Youth mentoring for young people at risk of exclusion from secondary school: a feasibility randomised controlled trial. (November 2016) - Beattie, Angela M; Busse, Heide; Kipping, Ruth R; Gunnell, David J; Hickman, Matthew; Macleod, John A A; Hollingworth, William; Berridge, David; Metcalfe, Chris; Campbell, Rona M
Abstract: Background: Youth mentoring is used with young people to help improve their health, wellbeing, and educational attainment. Despite the growing interest in mentoring programmes among policy makers and practitioners the evidence-base is weak, with no randomised controlled trial (RCT) yet undertaken in the UK. This study aimed to assess the feasibility and acceptability of conducting a definitive RCT of the effectiveness and cost-effectiveness of Breakthrough Mentoring, a council-supported programme that provides formal, one-to-one mentoring through paid, adult mentors. Methods: 31 secondary school students, judged by school staff to be at risk of exclusion, were approached and 21 (eight girls, 13 boys) were recruited to the study. Participants were aged 12–16 years (mean 14·1) and randomised to receive weekly 2 hour mentoring sessions for one academic year (n=11, intervention) or care as usual (ten, control). Participants were asked to complete self-reported questionnaires, including the Strength and Difficulties Questionnaire, which were analysed descriptively. Qualitative interviews were conducted with participants and with parents, schools staff, mentors, and commissioners as part of the process evaluation. Interviews were audio-recorded, transcribed verbatim, and analysed thematically. This trial is registered with the ISRCTN registry, number ISRCTN97394558. Findings: Follow-up at 6 and 12 months was 100%, and 86% (n=18) at 18 months. Participants were happy to complete the questionnaires and were accepting of the study design. Control participants reported wanting a mentor and some were mildly upset at not achieving this. Intervention participants indicated that having a mentor, unconnected to school, helped them talk about and deal with difficult feelings. Some reported negative experiences of the way that the mentoring relationship ended. The process evaluation showed that the study design and intervention were acceptable to parents, mentors, schools, and commissioners. Interpretation: The recruitment, randomisation, and retention of students at risk of exclusion from school to an RCT for 6, 12, and 18 months' follow-up is feasible and acceptable. Before a definitive trial can be considered, further research is required to characterise youth mentoring in the UK and to investigate how to best measure its effectiveness. Funding: This is a summary of independent research funded by the National Institute for Health Research School for Public Health Research.